Miniaturization of BaHfO3 nanoparticles in YBa2Cu3Oy-coated conductors using a two-step heating process in the TFA-MOD method. (29th December 2016) - Horita, H; Teranishi, R; Yamada, Kazuhiro; Kaneko, K; Sato, Y; Otaguro, K; Nishiyama, T; Izumi, T; Awaji, S
Abstract: The critical current density ( J c ) of YBa2 Cu3 Oy (YBCO)-coated conductors in a magnetic field can be enhanced by the doping of flux-pinning centers in a metal organic deposition (MOD) process with trifluoroacetates (TFA). The size of these flux-pinning centers should be less than 10 nm to achieve commercial use due to the coherence length of YBCO at 77 K. In this paper, BaHfO3 (BHO) nanoparticles were introduced into YBCO films using the TFA-MOD method. Microstructures and the  J c properties of the films prepared using a two-step heating process at crystallization were compared with film prepared using a conventional one-step heating process. The two-step heating process produced 15 nm average-sized BHO nanoparticles in the film compared to 19 nm nanoparticles in a film prepared using a one-step process. It was revealed that the size of nanoparticles in the films could be miniaturized by improving the heating processes in the MOD method, and the miniaturized nanoparticles could contribute to increased J c in magnetic fields. The mechanism of miniaturization is also discussed based on microstructure observations of quenched films.